Design and tests of a planetary non-circular gear train transplanting mechanism for flower plug seedlings - B. Ye; B. Ye; X. Wang; T. Tang; T. Tang; G. Zeng; Y. Zheng (Mechanical Sciences, 2025)
To address the problems relating to the low efficiency and high labor intensity of the manual operations required for transplanting potted flower plug seedlings in China, along with the lack of suitable transplanting machinery, an automatic bowl-clamping-type transplanting mechanism with a planetary gear train based on incomplete non-circular gear transmission is proposed. The mechanism design method, combining forward parameter modification (to guide optimization design) and reverse design, is applied to design the transplanting mechanism. The kinematic model and parameter modification guiding the optimization design model of the transplanting mechanism are established, and the parametric guidance optimization software is developed. The reverse design model of the transplanting mechanism is established, and the static trajectory of the return section obtained from the optimization design is fine-tuned and fitted with a cubic B-spline curve. The virtual motion simulation analysis of the transplanting mechanism is carried out to verify the correctness of the mechanism design. Transplanting tests demonstrated that the mechanism meets the requirements for transplanting flower plug seedlings, exhibiting good application feasibility.